(untitled) (Bangladesh Journal of Medicine, 2015)
A rare syndrome, Dyke-Davidoff-Masson Syndrome (DDMS), with a diagnostic conundrum, and the way it was solved is presented. DDMS is one among the syndromes associated with refractory epilepsy. We have come across a case of Dyke-Davidoff-Masson syndrome while investigating a case of refractory epilepsy. When cerebral hemi atrophy is associated with the radiological features of osseous hypertrophy of calvarium, hyper-pneumatisation of sinuses dilatation, DDMS is to be considered. Bangladesh J Medicine Jan 2014; 25 (1) : 31-34